MODERN LOVE ORIENTATION IN THE NOVEL "MAA LAA NABUUHU BIH" BY SANDRA SIRAJ: ORIENTASI CINTA MODERN DALAM NOVEL “MAA LAA NABUUHU BIH” KARYA SANDRA SIRAJ - Muhammad Zarnubi; Ahmad Kholil (Jurnal Kata, 2024)
This research aims to explain the orientation of modern love according to Erich Fromm in the novel “Maa Laa Nabuuhu Bih” by Sandra Siraj and reveal social facts that occur in real life. The method in this research is descriptive qualitative. The primary data source is the novel “Maa Laa Nabuuhu Bih” by Sandra Siraj published by Daar Dawen in 2018 totaling 174 pages.  While secondary data sources come from studies that are relevant to the discussion of this research. The data collection technique uses the reading and note-taking method. Then, the data is analyzed by uncovering, understanding, and getting messages from the quotations in the novel. From the results of this study, 8 love orientations were found with details of 1 receptive orientation, 1 exploitative orientation, 2 hoarding orientations, 4 market orientation data. Based on the results of this study, it can be concluded that there are still many couples who only focus on the personal benefits they will get without thinking about their partner's feelings, just like the story in the novel “Maa Laa Nabuuhu Bih” by Sandra Siraj.